Infectious keratoconjunctivitis associated with Pseudomonas aeruginosa infection in a fat-tailed sheep reared under semi-open housing conditions - Bagas Pria Prasetyo; I Putu Cahyadi Putra; Mettarani Dymia Euis Pefdini; Anis Pramundari (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2026)
Pink eye, or infectious keratoconjunctivitis, is a contagious disease that can impair vision and welfare if untreated. This case report describes the diagnosis and management of Pseudomonas aeruginosa-associated infectious keratoconjunctivitis in a sheep in Kulonprogo, Yogyakarta, Indonesia. A 3-year-old female fat-tailed sheep weighing 30 kg presented with bilateral redness for two days. Clinical examination revealed photophobia, corneal opacity, lacrimation, and conjunctival inflammation. Hematological examination revealed leukocytosis and neutrophilia, indicating an inflammatory reaction. Bacterial culture of a conjunctival swab identified P. aeruginosa, although antibiotic susceptibility testing was not performed. Based on the history, clinical signs, physical examination, hematological findings, and bacteriological confirmation, the sheep was diagnosed with infectious keratoconjunctivitis associated with P. aeruginosa infection and a favorable prognosis. Empirical treatment consisted of intramuscular dihydrostreptomycin sulfate–procaine penicillin G at 0.1 mL/kg body weight, intramuscular vitamin B12 at 0.01 mg/kg body weight, and topical oxytetracycline to both eyes. Improvement occurred two days after treatment, with reduced lacrimation and clearer corneas.